Prevalence of Obesity Among Type 2 Diabetes Patients Attending Diabetic Clinic in Nepalgunj Medical College Teaching Hospital - Parajuli, J; Swar, NB; Khadka, D; Thapa, N (Journal of Nepalgunj Medical College, 2015)
Background: Obesity and type 2 diabetes constitute major public health issues in modern societies worldwide. These two forms frequently coexist, and statistics show that 60–90% of all patients with type 2 diabetes are or have been obese. Obesity is generally considered to be a strong risk factor for the development of type 2 diabetes mellitus in future. Objectives: This study aims to assess the prevalence of obesity among type 2 diabetes patients attending diabetic clinic in Nepalgunj Medical College Teaching Hospital. Methods: An analytical cross-sectional study was conducted at NGMCTH, kohalpur, Nepal during the period from October 2013 to March 2014. The present study comprised of a total of 385 type 2 diabetic subjects whose BMI was measured during the visit to the diabetic clinic. Respondents' height, weight, age, sex and duration of diabetes were taken as the study variable. Results: Out of total, 51.4% were female and 48.6% were male who attended the clinic. The mean age of the study population was 56.20±11.95 (95% CI; 54.47-57.92) of which 38% were overweight, 4.2% were obese and 55.8% had normal BMI. The proportion of overweight in total population is 37.1% where female type 2 diabetes proportion (41.4%) was comparatively higher than male(32.6%). 4.2 % of the total type 2 diabetes were obese and above(p=0.014). Conclusions: High prevalence of overweight and obesity in type 2 diabetics is associated with other serious complications. Ways to control prevent obesity and overweight should be stressed and made known to people of all ages in the population. Journal of Nepalgunj Medical College Vol.12(1) 2014: 25-28